DESTRUCTIVE LEADERSHIP IN FOOTBALL: HOW TO PLAYERS PERCEIVE THEIR COACHES DARK SIDE? - Erdem, Kamil; Karagozoglu, Cengiz (Acta Scientiae et Intellectus, 2024)
Aim of this study was to investigate how to football players evaluate their coaches destructive leadership actions in relation with players characteristics. All male four hundred and sixteen football players participated and accepted to answer the Destructive Leadership Scale (DLS) (Uymaz, 2013) with a personal information form to get the demographic data. The participants consisted from all senior Turkish leagues including the Super League (n=63), League 1 (n=84), League 2 (n=135) and League 3 (n=134), the mean age was 25.27 (SD=4.31). The players’ position in the team were 44 goalkeepers, 134 defensive players, 179 middle field players and 59 offensive players. The six subscale of the DLS compared by league status, age group of players, educational status, working duration (in months) with the current coach, number of worked coaches during the career and the possibility of being in the first 11 players in last 3 months’ matches by ANOVA statistics. Before the statistical analyses, reliability coefficients of the DLS checked and there were satisfactory results. There was significant difference on the all six subscales (Excessive authority use, Lack of Leadership Competency, Lack of interest to subordinates, Resistence to technology and change, Unethical behavior and nepotism) comparing with the League Status variable. There was a bipolar distribution where Super League players and League 3 players’ subscale scores were mostly higher than League 1 and League 2 players. This result was interpreted as Super League and League 3 players mostly perceive their coaches more destructive than other leagues. Also the players who worked 0-2 years range with their coaches, percieved their coaches more nepotist and in lack of interest with their subordinates than the players who has 3-5 years of working years with their coaches.